Analyzing the Effective Structures on Development of the Rural Producing Cooperatives in Khorasan Razavi Province (From the view point of Experts) - Dr. Khadijeh Boozarjmehri; Maryam Hadizadeh Bazaz (جغرافیا و آمایش شهری منطقه‌ای, 2013)
The main purpose of this paper is to study the effective factors on development of Rural Producing Cooperatives in Khorasan Razavi Province.  For this purpose, the affective factors on the development of cooperatives were analyzed and studied in three dimensions of internal, external and structural dimension with SWOT model.  In this study, the identified 34 indictors were prioritized and weighted through interview and filling questionnaire with professionals and experts of cooperatives and by Antropy technique. In the present study, the main purpose is through applying the strategic planning process, while studying  the capabilities for development of producing cooperatives it is tried to provide solutions and identify applied strategies  The final result shows that aceptable strategies for the development of cooperatives are SO strategies, while WO strategies are placed at the second priority. The SO4 strategy with a score of 1.19 is the best strategy for the development of cooperatives. This strategy is practical with supporting financial resources, infrastructure and legal framework. WO1 strategy, however, with a score 1.17 is the most effective strategy after SO4 strategy. This strategy focuses on the financial and credit problems and more effective use of human and financial resources. The results of this research indicate that the performance of cooperatives is poor. It is evident that necessary infrastructures, provided by government can reduce potential problems and increase appropriate utilization of internal and external opportunities.